STRENGTHENING ENVIRONMENTAL BASED OF LOCAL WISDOM VALUES IN WOVEN BAMBOO HAT CRAFTS IN HISTORY LEARNING - Permana, Rahayu; Hidayat, Arief; Absor, Nur Fajar (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Lambung Mangkurat, 2023)
This study aims to analyze the values of local wisdom environment-based in bamboo hat crafts in history learning. The research method used in this study is descriptive qualitative with data collection techniques in the form of documentation or also known as literature review. The results of the study show that 1) the importance of instilling local wisdom values in students in learning history; 2) strengthening local wisdom based on the environment in the craft of woven bamboo hats can provide local insights to students in learning history; 3) learning history in schools will be richer in local content with local wisdom values based on the environment in the craft of woven bamboo hats.